2006
DOI: 10.1039/b611090h
|View full text |Cite
|
Sign up to set email alerts
|

Phosphazene base-promoted functionalization of aryltrimethylsilanes

Abstract: The activation of Ar-Si bonds in aryltrimethylsilane was investigated using a catalytic amount of t-Bu-P4 base and selective functionalizations of aryltrimethylsilanes in the absence of strong electron withdrawing groups on the aromatic rings were accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…31 Phthalides have been used as precursors for the synthesis of anthraquinones. Peterson Olefination.…”
Section: Tmsmentioning
confidence: 99%
“…31 Phthalides have been used as precursors for the synthesis of anthraquinones. Peterson Olefination.…”
Section: Tmsmentioning
confidence: 99%
“…However, the reaction has been limited to aryltrimethylsilanes with strong electron-withdrawing groups on the aromatic rings. It was found that t Bu-P4 base could be used as an excellent catalyst to activate organosilicon compounds and the selective conversions of aryltrimethylsilanes catalysed by t Bu-P4 base have been investigated [57]. The reaction of 1-trimethylsilylnaphthalene with pivaldehyde in the presence of 20 mol% t Bu-P4 base proceeded smoothly at room temperature to give the alcohol in 91% yield.…”
Section: Generation Of Aryl Anion From Arylsilanementioning
confidence: 99%
“…Reactions with other aldehydes have been examined; that with benzaldehyde was found to proceed somewhat slowly at room temperature. Other aryl aldehydes with electron-donating groups were also employed as electrophiles and the reactions proceeded smoothly at room temperature [57] (Table 5.5).…”
Section: Generation Of Aryl Anion From Arylsilanementioning
confidence: 99%
See 1 more Smart Citation
“…In connection with our recent study on the selective transformation of arylsilanes, [3] we investigated the selective silylation of aryl halides with various functional groups catalysed by palladium.…”
Section: Introductionmentioning
confidence: 99%